A power series approach for hybrid-duplex UAV communication systems under rician shadowed fading - Madhukumar, A. S. (2019)
A hybrid-duplex (HBD) UAV communication system (UCS), i.e., HBD-UCS, to improve spectrum utilization is investigated in this work. By considering the combined effect of fading and shadowing, a comprehensive outage probability analysis of the HBD-UCS under various inter-UAV interference and shadowing scenarios over Rician shadowed fading channels is conducted. It is demonstrated that the ground station (GS) in full-duplex (FD) mode operates at lower outage probability than in half-duplex (HD) mode. Furthermore, the joint detector is shown to achieve lower outage probability than the interference ignorant (II) detector and HD-UCS, even when severe shadowing is encountered. As such, utilizing joint detectors in an HBD-UCS enables multi-UAV networks to achieve high reliability when operating in urban environments.